Plant Life of the Dolomites Vegetation Tables - Pignatti, Erika; Pignatti, Sandro (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This volume provides an in-depth analysis of over 100 plant communities of the Dolomite vegetation. The data is based on the phytosociological relevés, which have been collected by the authors in nearly 2000 surveys. The key part consists of approx. 130 association tables presenting plant sociological data for the respective plant communities. Thus, this volume perfectly complements the successful main volume "Plant Life of the Dolomites: Vegetation Structure and Ecology," which features summarized, synoptic association tables of the twelve habitats. In addition, geo-referenced locations of relevés and detailed ecological measures are provided. A further part describes the individual components of the fascinating dolomitic landscape (Heritage of all Humanity) and presents tables of vegetation complexes, which summarize the more than 400 surveys carried out in the Dolomites. The structure of this supplementary volume corresponds to that of the main volume with a key part consisting of twelve chapters, each describing a specific habitat, and a total of 106 associations. Several topics covered in the main volume, such as the exploration of the flora, ecological factors and syntaxonomy are discussed further here.